A concerted DNA methylation/histone methylation switch regulates rDNA gene dosage control and nucleolar dominance - Silva, Manuela (2004)
Eukaryotes regulate the effective dosage of their ribosomal RNA (rRNA) genes, expressing fewer than half of the genes at any one time. Likewise, genetic hybrids displaying nucleolar dominance transcribe rRNA genes inherited from one parent but silence the other paraental set.We show that rRNA gene dosage control and nucleolar dominance utilize a common mechanism